ANALISIS PENERAPAN PENYUSUNAN LAPORAN KEUANGAN PADA USAHA KECIL DAN MENENGAH (UKM) BERBASIS STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) DALAM MEMPEROLEH PEMBIAYAAN KREDIT - Nina Yulianasari (Jurnal Ilmu Akuntansi, 2020)
This study aims to determine how the application of financial statement preparation for small and medium-sized businesses (SMEs) based on SAK ETAP in obtaining credit financing at the City of Bengkulu gift shop with data collection techniques, namely interviews and documentation. From the results of interviews and documentation, it was found that the Central SMEs Gift of Taste of the City of Bengkulu is quite feasible to obtain credit financing, this is seen from the financial statements presented in accordance with the Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP). As for the obstacles faced by UKM Sentral By Cita Rasa Bengkulu City in the preparation of financial reports that refer to SAK ETAP namely the lack of qualified human resources and the lack of organization of steps in preparing financial reports.